Kidney transplant tolerance associated with remote autologous mesenchymal stromal cell administration. (24th December 2019) - Casiraghi, Federica; Perico, Norberto; Gotti, Eliana; Todeschini, Marta; Mister, Marilena; Cortinovis, Monica; Portalupi, Valentina; Plati, Anna Rita; Gaspari, Flavio; Villa, Alessandro; Introna, Martino; Longhi, Elena; et al.
Abstract: Here we report the case of successful immune tolerance induction in a living-donor kidney transplant recipient remotely treated with autologous bone marrow-derived mesenchymal stromal cells (MSC). This case report, which to the best of our knowledge is the first in the world in this setting, provides evidence that the modulation of the host immune system with MSC can enable the safe withdrawal of maintenance immunosuppressive drugs while preserving optimal long-term kidney allograft function. : Abstract : This report provides the evidence that autologous BM-MSC infusion induces a pro-tolerogenic immune environment, thus allowing complete discontinuation of antirejection drugs in kidney transplantation